DIAGNOSTICS, DIFFERENTIAL DIAGNOSTICS AND TREATMENT OF PANDAS SYNDROME: DESCRIPTION OF THE CASE (ResearchJet Journal of Analysis and Inventions, 2021)
This article gives a case of PANDAS syndrome in an 11-year-old boy. The course and clinic of the disease in the form of prolonged bouts of sneezing made it difficult to diagnose this syndrome. Biochemical blood tests, 24-hour video electroencephalographic monitoring (EEG monitoring) and magnetic resonance imaging of the brain (MRI) made it possible to determine the condition. Prescription of antibiotic therapy and intravenous administration of immunoglobulin led to remission of the disease. It is necessary to conduct further research to determine the effectiveness of the above drugs introduced above for this syndrome.